Banking of AT-MSC and its Influence on Their Application to Clinical Procedures - Semenova, Ekaterina; Grudniak, Mariusz P.; Bocian, Katarzyna; Chroscinska-Krawczyk, Magdalena; Trochonowicz, Marzena; Stepaniec, Igor M.; Murzyn, Magdalena; Szablowska-Gadomska, Ilona; Boruczkowski, Dariusz; Oldak, Tomasz; Machaj, Eugeniusz K. (Frontiers in Bioengineering and Biotechnology, 2021)
Processing of MSCs to obtain a therapeutic product consists of two main steps: a) the in vitro expansion of the cells until an appropriate number of them is obtained, and b) freezing and storage of the expanded cells. The last step is critical and must be optimized so that after thawing the cells retain all their physiological properties including the secretory function. In this paper, we evaluated physiological parameters of AT-MSC’s after a full cycle of their processing, particularly freezing and storing at the liquid nitrogen vapor temperature. Based on the recovered proliferative and secretory capacities of the thawed cells, we have designed the optimal technique for processing of MSCs for clinical applications. In our work, we tried to select the best DMSO-based cryoprotectant mixture on the base of post thawing AT-MSC investigation at the cellular, molecular and physiological levels, and consider whether the cells after thawing fully retain their properties. We have demonstrated the effectiveness of the use of DMSO in various configurations of the constituent cryoprotective fluids. We have also shown that AT-MSCs that show control levels in most standard tests (viability, shape, culture behaviour, and proliferative properties) after thawing, may show transient variations in some important physiological properties, such as the level of secreted growth factors. Obtained results let us to indicate how to optimize the AT-MSC preparation process for clinical applications. We suggest that before their clinical application the cells should be cultured for at least one passage to recover their physiological stability and thus assure their optimal therapeutic potential.